Glycosylation of Twisted Gastrulation is Required for BMP Binding and Activity during Craniofacial Development - Billington, Charles J.; Fiebig, Juliane; Forsman, Cynthia L.; Pham, Lan; Burbach, Nathan; Sun, Mu; Jaskoll, Tina; Mansky, Kim; Gopalakrishnan, Rajaram; O'Connor, Michael B.; Mueller, Thomas; Petryk, Anna (Frontiers in Physiology, 2011)
Twisted Gastrulation (TWSG1) is a conserved, secreted glycoprotein that modulates signaling of bone morphogenetic proteins (BMPs) in the extracellular space. Deletion of exon 4 of mouse Twsg1 (mTwsg1) is associated with significant craniofacial defects. However, little is understood about the biochemical properties of the corresponding region of the protein. We have uncovered a significant role for exon 4 sequences as encoding the only two glycosylation sites of the mTWSG1 protein. Deletion of the entire exon 4 or mutation of both glycosylation sites within exon 4 abolishes glycosylation of mTWSG1. Importantly, we find that constructs with mutated glycosylation sites have significantly reduced BMP binding activity. We further show that glycosylation and activity of TWSG1 recombinant proteins vary markedly by cellular source. Non-glycosylated mTWSG1 made in E. coli has both reduced affinity for BMPs, as shown by surface plasmon resonance analysis, and reduced BMP inhibitory activity in a mandibular explant culture system compared to glycosylated proteins made in insect cells or murine myeloma cells. This study highlights an essential role for glycosylation in Twisted gastrulation action.